Mudanças de cenário e impactos na cultura organizacional em uma instituição de ensino superior. - Silva, Simone Almeida da (2013)
This dissertation had as the main objective to analyze the changes that happened in the organizational culture of Pró-Reitoria de Gestão de Pessoas - PROGEP - of Federal University of Paraíba, according to the perception of organizational people, during the last ten years, after the proposal of a new management model called Gespública, as well as the renovation of the organizational staff by means of new signings and terminations of former civil servants. In order to reach this aim, the following specific objectives were established: a) Identify, through the perception of the research subject, the profile of the culture in the organizational unit before the changes; b) Identify, through the perception of the research subject, the profile of the culture in the organizational unit after the changes; c) Analyze the possible cultural changes which happened with the changes; d) Analyze if the possible cultural changes which happened can contribute to attend the new principles proposed by Gespública. This study was addressed from the perspective of the organizational based on the Organizational culture architecture model Marco and directed by the quantitative approach, being that for the data collect it was used the questionnaire as instrument and for data analysis the descriptive statistic, as well as parametric and non-parametric tests of media comparison. The results showed that even with the events of the new management model called Gespública, as well as with the renovation of the organizational staff that could promote the replacement or the acculturation of the subjects, no change was detected in the researched Pró-Reitoria. In the end, some recommendations and implications were presented, aiming to contribute to the development of researches involving organizational culture in public institutions.